1961
DOI: 10.1111/j.1365-2818.1961.tb05227.x
|View full text |Cite
|
Sign up to set email alerts
|

CYTOLOGY OF SPERMATOGENESIS IN THE HONEY‐BEE, APIS INDICA (F.)

Abstract: ~T E S XCVIII-C AND THBEE TEXT-FIQWES SYNOPSISThe spermatogenesis of the honey-bee, Apia indiea (F.), has been worked out with special referenceThe haploid number of sixteen chromosomes in the parthenogenetic malea remains constant throughMeiosis I is abortive, resulting in the formation of a definite non-nucleated cytoplasmic bud containingThe significance of an extra-and an intra-nuclear spindle in relation to the abortive meiosisisdisouased. Meiosis I1 is normal 80 far aa the nuclear division is concerned. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
4
13
0
Order By: Relevance
“…The present cytological findings on the common Indian formicid ant, Camponotus compressus, are in continuation of the the author's earlier work on the cytology of the honey-bees, Apis indica (SHARMA et al, 1961) and A. dorsata (KuMBKARNI 1964), and the carpenter-bee, Xylocopa fenesterata (KuMBKARNI 1965a).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…The present cytological findings on the common Indian formicid ant, Camponotus compressus, are in continuation of the the author's earlier work on the cytology of the honey-bees, Apis indica (SHARMA et al, 1961) and A. dorsata (KuMBKARNI 1964), and the carpenter-bee, Xylocopa fenesterata (KuMBKARNI 1965a).…”
Section: Introductionsupporting
confidence: 67%
“…However, the existence of this clumping, as a persistent and genuine feature, has been confirmed by studying the living cells also under the phase-contrast microscope during present investigations and in Apis indica (SHARMA, GuPTA and KuMBKARNI 1961). The chromosomes mostly lose all visible individual identity.…”
Section: Cytology Of Spermatogenesismentioning
confidence: 67%
“…The second division is mitotic and results in two functional sperm. In bees, the second meiotic division is unequal and results in a functional sperm and a nonfunctional cell which degenerates (Sharma et al 1961). In haplodiploid scolytids (Coleoptera) there are two mitotic divisions in spermatocytes (White 1973).…”
Section: Discussionmentioning
confidence: 99%
“…However, the maturation division during spermatogenesis is altered in haploid males. Ultrastructural and cytological observations of spermatogenesis in bees and wasps indicated that the reductional division in meiosis I is aborted, but the equational division (meiosis II) is maintained to produce haploid sperm (Sharma et al, 1961;Hoage and Kessel, 1968;Hogge and King, 1975;Cruz-Landim et al, 1980). Recent progress in genome analysis has revealed the presence of meiosis-related genes in hymenopterans and other arthropods (Schurko et al, 2009;Schurko et al, 2010;The Honeybee Genome Sequencing Consortium, 2006;Werren et al, 2010).…”
Section: Introductionmentioning
confidence: 97%